International Workshop on Ionizing and Non-Ionizing Radiation Influence on Structure and Biophysical Properties of Living Cells (Tsaghkadzor, Armenia, September 25-27, 2015)
Proceedings. Invited Editor - Dr. H. Badalyan
Keywords: Physics; Cross-Disciplinary